2014
DOI: 10.3390/molecules191117829
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anticancer Aporphine Alkaloids from the Leaves of Nelumbo nucifera Gaertn. cv. Rosa-plena

Abstract: Fifteen compounds were extracted and purified from the leaves of Nelumbo nucifera Gaertn. cv. Rosa-plena. These compounds include liriodenine (1), lysicamine (2), (-)-anonaine (3), (-)-asimilobine (4), (-)-caaverine (5), (-)-N-methylasimilobine (6), (-)-nuciferine (7), (-)-nornuciferine (8), (-)-roemerine (9), 7-hydroxydehydronuciferine (10) cepharadione B (11), β-sitostenone (12), stigmasta-4,22-dien-3-one (13) and two chlorophylls: pheophytin-a (14) and aristophyll-C (15). The anti-oxidation activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 24 publications
3
69
0
1
Order By: Relevance
“…As a pilot study, the anti-tumor activities and molecular mechanisms of nuciferine, an aporphine alkaloid extracted from lotus leaves, were selected for further study and validation in our investigation, on the basis of evidence from the literature and in vivo/in vitro experiments. For example, nuciferine has been reported in studies of melanoma [16] , non-small cell lung cancer [17] and the DU-145 cell line [18] . In addition, we predicted that nuciferine and melphalan would exhibit similar anti-tumor profiles against the tested tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…As a pilot study, the anti-tumor activities and molecular mechanisms of nuciferine, an aporphine alkaloid extracted from lotus leaves, were selected for further study and validation in our investigation, on the basis of evidence from the literature and in vivo/in vitro experiments. For example, nuciferine has been reported in studies of melanoma [16] , non-small cell lung cancer [17] and the DU-145 cell line [18] . In addition, we predicted that nuciferine and melphalan would exhibit similar anti-tumor profiles against the tested tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…cv. Rosa-plena exhibited antioxidant and anticancer activity in vitro (30). In the present study, BLSA exhibited anti-cancer effects, associated with the induction of apoptosis, in CNE-1 cells.…”
Section: Discussionmentioning
confidence: 73%
“…Sequential fractionation of active extracts with organic solvents, for example, petroleum ether, acetone, dichloromethane, ethyl acetate, butanol and methanol (Khlifi et al 2013;Tagne et al 2014) has also been reported. The cytotoxicity assay most widely used for estimating the anticancer potential of EFM is the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (Babykutty et al 2008;Fan et al 2014;Liu et al 2014;Park et al 2005), but other assays such as the sulphorhodamine B (SRB), neutral red, and lactate dehydrogenase (LDH) leakage assays have also been used (Aboul-Enein et al 2014;Prasad et al 2005;Rose et al 2005). The MTT assay gives an indication of whole cell cytotoxicity.…”
Section: Common Experimental Approachesmentioning
confidence: 98%